Análise do potencial das redes de informações turísticas nos sites dos governos do Brasil e da Bolívia - Miranda, Amli Paula Martins de (2011)
Information technology and communication, by itself, does not have the power to make a revolution in society, but possible changes in the economic, political, ethical and cultural order. The new configuration is based on a global network of cooperation and information, changing concepts used previously in a world structured by traditional geographic boundaries. One of the sciences that have been adapting to this new configuration is the Geography that, with the Geography of Cyberspace, will map the networks of information and cooperation and inter-human relationships through the digital world, seeking to understand how they form the new virtual territories and territorialities. Tourism is one of the activities that seek to track changes because is globalizing by itself. Cyberspace tour also involves relations of power and requires reflections about the role of communication for development of the activity and the balance between social actors. The dissertation aims to map and analyze the potential of formation and range of the information networks of the governments sites of Brazil and Bolivia, seeking to understand how connections are formed and propagate in cyberspace. The sites selected were the Ministry of Tourism of Brazil, State Secretary of Tourism Development of Mato Grosso, Tourism Foundation of Mato Grosso do Sul, Ministry of Culture of Bolivia, Autonomous Municipal Government of La Paz and Autonomous Municipal Government of Copacabana. The research studies the potencial of the formation of virtual networks using the techniques of Geographic Information System (GIS) coupled with information of the administrators using its own tools developed by governments and the Google Analytics, a service offered by Google to monitor sites, wich provides access statistics. From the analysis and evaluation of the results of the map produced with the recognition of the potencial tourist information networks, this dissertation seeks to encourage the emergence of new methods for investigating the research topic with the enrichment of current concepts. Sharing knowledge and disseminating information, this research proposes debates the possible creation of a tourism network in the Brazil-Bolivia along the lines of internet social networks. This work will be proposed the creation of a research group about Geography of Cyberspace in UFMT, trying to make it possible to create channels of communication and a collection of easily accessible information about the virtual territories formed on the internet to encourage the regional development.